Governance Indicators : Where Are We, Where Should We Be Going? - Kaufmann, Daniel; Kraay, Aart (World Bank, Washington, DC, 2012)
Scholars, policymakers, aid donors, and aid recipients acknowledge the importance of good governance for development. This understanding has spurred an intense interest in more refined, nuanced, and policy-relevant indicators of governance. In this paper we review progress to date in the area of measuring governance, using a simple framework of analysis focusing on two key questions: (i) what do we measure? and, (ii) whose views do we rely on? For the former question, we distinguish between indicators measuring formal laws or rules 'on the books', and indicators that measure the practical application or outcomes of these rules 'on the ground', calling attention to the strengths and weaknesses of both types of indicators as well as the complementarities between them. For the latter question, we distinguish between experts and survey respondents on whose views governance assessments are based, again highlighting their advantages, disadvantages, and complementarities. We also review the merits of aggregate as opposed to individual governance indicators. We conclude with some simple principles to guide the refinement of existing governance indicators and the development of future indicators. We emphasize the need to: transparently disclose and account for the margins of error in all indicators; draw from a diversity of indicators and exploit complementarities among them; submit all indicators to rigorous public and academic scrutiny; and, in light of the lessons of over a decade of existing indicators, to be realistic in the expectations of future indicators.